2013
DOI: 10.1007/s11695-012-0850-6
|View full text |Cite
|
Sign up to set email alerts
|

Radical Resection of the Pyloric Antrum and Its Effect on Gastric Emptying After Sleeve Gastrectomy

Abstract: In the RA group, an increase in gastric emptying postoperatively was noted. Complications such as failure of stomach evacuation were not observed in the RA group. Our results suggest that even more radical resection of the pyloric antrum performed by LSG is possible without concerns of postoperative disorder of the stomach evacuation function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 36 publications
3
32
0
3
Order By: Relevance
“…Similar gastric emptying rates were observed for MO and nonobese individuals but a highly accelerated rate for SG patients; this result agrees with some studies (8, 9, 29) but contradicts others (30,31), which suggested that antrum size after SG could influence gastric emptying. Some authors have hypothesized that higher intragastric pressure (32) with less peristalsis of the sleeve and faster propagation of antral propulsion waves (33) may play a role in this accelerated emptying.…”
Section: Discussionsupporting
confidence: 89%
“…Similar gastric emptying rates were observed for MO and nonobese individuals but a highly accelerated rate for SG patients; this result agrees with some studies (8, 9, 29) but contradicts others (30,31), which suggested that antrum size after SG could influence gastric emptying. Some authors have hypothesized that higher intragastric pressure (32) with less peristalsis of the sleeve and faster propagation of antral propulsion waves (33) may play a role in this accelerated emptying.…”
Section: Discussionsupporting
confidence: 89%
“…They found that differences in the average values of weight, BMI, or %EWL between the 2 groups were not statistically significant. However, they concluded that even after a radical resection of the pyloric antrum, the physiologic stomach evacuation function can still be preserved [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains to be established, VSG-mediated increased gastric emptying or RYGB-induced redirection of intestinal nutrient flow could therefore possibly lead to enhanced L-cell responsiveness to glucose, as well as amino acids and bile acids. Indeed, VSG surgery procedures promote increased gastric emptying rates in rodents [78], [79] as well as in humans [80], [81], [82]. Nevertheless, the VSG procedure maintains delivery of macronutrients within the proximal duodenum which exhibits very few, if any, GCG-expressing cells.…”
Section: Discussionmentioning
confidence: 99%